2005
DOI: 10.1111/j.1365-3040.2005.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ethylene in the regulation of cell death and leaf loss in ozone‐exposed European beech

Abstract: To test the involvement of ethylene in mediating ozoneinduced cell death and leaf loss in European beech ( Fagus sylvatica L.), tree seedlings were exposed to proportionally increased or decreased field ozone levels for up to 6 months. Ozone treatment caused cell death and accelerated leaf loss at higher than ambient levels, but had only minor effects at ambient and no effects at subambient ozone levels. The emission of ethylene, the levels of its precursor, 1-aminocyclopropane-1-carboxylate (ACC), and mRNA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…ACC oxidases, were up-regulated. This oxidative stress response could also be seen in beech saplings (Nunn et al 2005a), three different tomato-cultivars (Moeder et al 2002) and in A. thaliana ecotype Col-0, and Wassilewskija (Li et al 2006) where transcripts of ACC-oxidases increased upon ozone exposure. In contrast, in A. thaliana ecotype Columbia four ACCoxidases were not affected by ozone (D'Haese et al 2006), and in ozone-sensitive Medicago trunculata ecotype Jemalong, genes associated with ET-signalling were reduced (Puckette et al 2008).…”
Section: Real-time Quantitative Rt-pcr Analysis (Qrt-pcr) Versus Micrmentioning
confidence: 86%
“…ACC oxidases, were up-regulated. This oxidative stress response could also be seen in beech saplings (Nunn et al 2005a), three different tomato-cultivars (Moeder et al 2002) and in A. thaliana ecotype Col-0, and Wassilewskija (Li et al 2006) where transcripts of ACC-oxidases increased upon ozone exposure. In contrast, in A. thaliana ecotype Columbia four ACCoxidases were not affected by ozone (D'Haese et al 2006), and in ozone-sensitive Medicago trunculata ecotype Jemalong, genes associated with ET-signalling were reduced (Puckette et al 2008).…”
Section: Real-time Quantitative Rt-pcr Analysis (Qrt-pcr) Versus Micrmentioning
confidence: 86%
“…High ozone levels can be detrimental to leaves of sensitive plants by causing reduced photosynthesis (Lippert et al 1996;Pell et al 1997;Grams et al 1999;Paoletti et al 2002;Nunn et al 2005a). Moreover, even low ozone doses over longer time periods evoke oxidative plant stress (Matyssek and Sandermann 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Physiological reactions in ozone challenged leaves are induction of anti-oxidants and stress related enzymes (Polle et al 2000;Wustman et al 2001;Langebartels et al 2002b;Sandermann and Matyssek 2004;Herbinger et al 2005;Nunn et al 2005a). Carbon and energy equivalents required for these defence reactions are no longer available for plant growth resulting in lowered productivity (Dizengremel 2001), which typically results in reduced growth especially of ozone sensitive plants (King et al 2005;Kozovits et al 2005a).…”
Section: Introductionmentioning
confidence: 98%
“…Ozone exposure of 3-year-old European beech saplings over a period of 7 weeks (0.06 to 0.150 μl/l, 10 h/d) resulted in an accumulation of extensin transcripts in 5-month-old leaves (Schneiderbauer et al, 1995). Recently it was shown that exposure of 4-year-old European beech saplings to 0.2 μl/l ozone over a period of 46 d resulted in an increased transcript level for ACC synthase and ACC oxidase, whereas ribulose bisphosphate carboxylase small subunit was not altered (Nunn et al, 2005). Knowledge about the molecular mechanisms at the level of gene expression is important to understand an environmental impact, e.g., ozone, on forest trees (Matyssek et al, 2004;Sandermann and Matyssek, 2004).…”
Section: Introductionmentioning
confidence: 99%